More about university education, employment and recession - Moreiro-González, José-Antonio (Anuario ThinkEPI, 2014)
Analysis of the status of the professions of librarian, documentalist and information scientis tin Spain, studying the influence of the curriculum in the labour market. Forty percent of employers believe that graduates should have more knowledge about specific sources of information: legal, economic, health, education, etc. The profession and its programme of studies are poorly understood by society, and the terminological inconsistency between degree titles, the field of knowledge and professional institutions contributes to this problem. The number of graduates in Spain reached its maximum in 2005 (1,727) and this amount has steadily declined, to 667 in 2012.
Keywords: University studies; Library and Information Science; Diploma; Degree; Information; Labour market; Unemployment; Social recognition; Professional recognition.